Elliptical and circular bonded composite repair under mechanical and thermal loading in aircraft structures - Faycal Benyahia; Abdulmohsen Albedah; Bel Abbes Bachir Bouiadjra (Materials Research, 2014)
In this study, the three-dimensional finite element method is used to achieve a comparison between the semi circular and semi elliptical patch repairs in aircraft structures. The comparison was done by the analysis of : the mechanical and thermal stress intensity factors (SIF and TSIF) at the tip of repaired crack and the distribution of the adhesive stresses for the two patch shapes. The obtained results show that the semi circular shape of the patch presents lower stress intensity factor at the crack tip, which is beneficial for the fatigue life and lower adhesives stresses, which is beneficial for the repair durability. In addition the circular patch is subjected to less significant thermal residual stresses compared to the elliptical shapes.